Nursing research in Brazil: the client with arterial hypertension or at risk - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2002)
Uncontrolled high blood pressure is a major public health problem in Brazil, particularly among African-Brazilian people. Despite the advances related to the prevention and control of the disease, many clients are still suffering with the morbity or the mortality of the arterial hipertension and others present the risk factors related to cardiovascular diseases.